Deletion of Rap‐Phr systems in Bacillus subtilis influences in vitro biofilm formation and plant root colonization. Issue 3 (27th June 2021) - Nordgaard, Mathilde; Mortensen, Rasmus Møller Rosenbek; Kirk, Nikolaj Kaae; Gallegos‐Monterrosa, Ramses; Kovács, Ákos T.
Abstract: Natural isolates of the soil‐dwelling bacterium Bacillus subtilis form robust biofilms under laboratory conditions and colonize plant roots. B. subtilis biofilm gene expression displays phenotypic heterogeneity that is influenced by a family of Rap‐Phr regulatory systems. Most Rap‐Phr systems in B. subtilis have been studied independently, in different genetic backgrounds and under distinct conditions, hampering true comparison of the Rap‐Phr systems' impact on bacterial cell differentiation. Here, we investigated each of the 12 Rap‐Phr systems of B.subtilis NCIB 3610 for their effect on biofilm formation. By studying single ∆ rap ‐ phr mutants, we show that despite redundancy between the cell–cell communication systems, deletion of each of the 12 Rap‐Phr systems influences matrix gene expression. These Rap‐Phr systems therefore enable fine‐tuning of the timing and level of matrix production in response to specific conditions. Furthermore, some of the ∆ rap ‐ phr mutants demonstrated altered biofilm formation in vitro and colonization of Arabidopsis thaliana roots, but not necessarily similarly in both processes, indicating that the pathways regulating matrix gene expression and other factors important for biofilm formation may be differently regulated under these distinct conditions. Abstract : Bacillus subtilis NCIB3610 contains 12 cell–cell signaling Rap‐Phr systems that influence cell differentiation. Here, we systematically investigate how each of these systems impacts biofilm formation by studying WT and the 12 single ∆ rap‐phr mutants in different phenotypic assays. Our approach revealed that while all 12 Rap‐Phr systems affect matrix gene expression, only certain Rap‐Phr systems influence the development of in vitro biofilms and root colonization, the latter representing an ecologically relevant environment for this bacterium.